2012
DOI: 10.1097/brs.0b013e31826c72b4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3 Reconstructive Techniques in the Surgical Management of Multilevel Cervical Spondylotic Myelopathy

Abstract: The HDF can be considered an effective and safe alternative procedure compared with ACDF in the treatment of the multilevel CSM, and ACCF should be the last option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
102
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 20 publications
4
102
1
1
Order By: Relevance
“…Some reports suggested that 2-level ACCF is associated with complication rates that are as much as 22% higher than that of ACDF. 6,14 Other studies, however, have shown no difference in complication rates between ACCF and ACDF. 13,20 However, one must emphasize again that drawing conclusions from these studies is limited because they do not specifically address the utilization of PSF.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Some reports suggested that 2-level ACCF is associated with complication rates that are as much as 22% higher than that of ACDF. 6,14 Other studies, however, have shown no difference in complication rates between ACCF and ACDF. 13,20 However, one must emphasize again that drawing conclusions from these studies is limited because they do not specifically address the utilization of PSF.…”
Section: Discussionmentioning
confidence: 95%
“…6,13,14,20 Although multiple studies have shown increases in blood loss associated with ACCF, the clinical significance is questionable because the amount of additional blood loss is relatively small (ranging from an additional 46 ml to 273 ml). This volume usually does not warrant blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past few years, cervical motion preserved through implantation of artificial disc prosthesis has been proved to be an effective and safe alternative option in 1 and 2 level pathologies [10,17,23,39]. However, anterior cervical discectomy and fusion (ACDF) remains the gold standard in the surgical treatment of the patients with multilevel CSM, resulting in well established results and less complications [19,28,36]. The use of stand-alone cage technology in cervical spondylosis was first introduced by Bagby [1].…”
Section: Discussionmentioning
confidence: 99%